- Increasing the Independence of Oyster Mushroom (Pleurotus ostreatus) Entrepreneurs in Seedlings Preparation: - - Hasanah, Yaya (Journal of Saintech Transfer, 2023)
Sadam Mushroom House is one of the mushroom producers in Medan Marelan with oyster mushroom production of 7-12 kg/day and can accommodate 7,000 baglogs. The problem of the oyster mushroom business is still very dependent on mushroom nurseries in an effort to provide F2 seedlings because there are still very limited facilities, infrastructure, understanding and skills in providing F0 - F2 seeds. Another problem is that the baglogs waste produced (2,000-3,000 baglogs every 3 months) has not been used properly so that it has the potential to pollute the environment. The purpose of this community service is to increase the independence of partners in providing oyster mushroom seeds, making compost from baglog waste and its use in plant cultivation. The solutions offered in solving these problems are the introduction of appropriate technology in the supply of F0-F2 mushroom seeds, the introduction of technology transfer goods, the management of baglog waste into compost and the use of compost from baglog waste as organic fertilizer for plant cultivation. The results of the community service that have been achieved are the introduction of technology transfer goods in the form of an autoclave, simple laminar air flow and tools for providing F0-F2 seedlings, training and assistance in providing F0-F2 mushroom seedling, training and assistance in making compost from baglog mushroom waste, direct practice of using mushroom compost for cultivating mung bean crop.